Mechanics of fluid flow - Basnijev, Kaplan Saferbijevič; Dmitrijev, Nikolaj Michajlovič, 1948-; Chilingar, George V., 1929- (Wiley ; Scrivener, 2012)
"The mechanics of fluid flow is a fundamental engineering discipline explaining both natural phenomena and human-induced processes, and a thorough understanding of it is central to the operations of the oil and gas industry. This book, written by some of the world's best-known and respected petroleum engineers, covers the concepts, theories, and applications of the mechanics of fluid flow for the veteran engineer working in the field and the student, alike. It is a must-have for any engineer working in the oil and gas industry."--Resumé vydavatele
Keywords: mechanika tekutin; mechanika kontinua; dynamika tekutin; fluid mechanics; continuum mechanics; fluid dynamics; monografie; elektronické knihy; monographs; electronic books